Genetic divergence of Etlingera elatior based on agro-morphological features for cut flowers - Gonçalves, Charleston; Colombo, Carlos Augusto; Castro, Carlos Eduardo Ferreira (Ornamental Horticulture, 2014)
Despite the wide acceptability Torch Ginger (Etlingera elatior) by the consumer market and its cultivation are still restricted due to the high mass of inflorescences (over 1 kg), which complicates the process of harvesting, handling, packaging and transportation. The objective of this work was to characterize agromorphological and estimate the genetic divergence among Etlingera elatior ( Jack) R.M. Sm. with standard cut flower. A stand of 75 genotypes resulting from crosses between genotypes at random from the collection of germplasm with variability inflorescences of commercial interest, they keep on growing in the Research and Development of Ubatuba. Seventeen descriptors were evaluated on the leaf, inflorescence and infrutescence. The inflorescence mass, length and diameter of the flowering stem, height and flower diameter were selected as the most important descriptors for selecting accessions with standard marketing as cut flower. We selected 12 promising accessions, with characteristics appropriate to the market and with good combination of shapes and coloring bracts.